Online solid phase extraction-LC-MS/MS with two step peak focusing for sensitive multi-analyte analysis of mycotoxins in urine - Kuhn, Michael; Kyei, Nicholas N. A.; Cramer, Benedikt; Humpf, Hans-Ulrich (Microchemical journal, 2025)
Mycotoxins are food contaminants that may pose a risk to human health. Biomonitoring of mycotoxins is a valuable tool to assess this potential risk and to evaluate the effect of mitigation strategies against mycotoxin exposure. Comprehensive exposure assessment requires sensitive multi-analyte methods that achieve low limits of detection (LOD) in physiological samples, while not becoming laborious with the high sample numbers required for high-quality biomonitoring studies. Online solid phase extraction (SPE) coupled to liquid chromatography with tandem mass spectrometry (LC-MS/MS) is a technique that can meet these demands, but requires careful optimization. We have developed and validated an online SPE-LC-MS/MS method covering 36 relevant mycotoxin biomarkers of exposure, mycotoxins, and mycotoxin metabolites. Optimized sample loading and washing on the reversed-phase polymeric SPE column ensured matrix removal and enrichment of structurally diverse analytes. In two separate steps, first the highly polar deoxynivalenol along with its glucuronides, followed by the remaining less polar mycotoxins, were transferred and refocused on the head of the analytical column by flow dilution using a mixing tee. LODs in the low pg/mL to low ng/mL urine range were reached, greatly improving sensitivity over established dilute-and-shoot methods. Stable isotope-labelled internal standards assured accurate quantification for 14 analytes, while the remaining analytes were quantified using matrix calibration. Reliable measurements were possible with intra- and inter-day precision values at three spiking levels ≤20 % for 21 analytes. The group of enniatins (A, A1, B, B1) and beauvericin exerted highly variable matrix effects among urine samples, allowing for only estimated quantitative results. Applying the method to a cohort of 50 pregnant women from Bangladesh demonstrated improved performance, with a 304 % increase in positive detections compared to a commonly used dilute-and-shoot approach.